Hipnoterapi Teknik Regression Therapy Untuk Menangani Penderita Glossophobia Siswa Sekolah Menengah Pertama - Atrup, Atrup; Fatmawati, Dwi (Universitas Nusantara PGRI Kediri, 2018)
Observations in one of the junior high schools in Kediri showed almost every class of students who were afraid to speak in public (glossophobia). This is shown when appointed to answer the question of whether they are silent, or when the teacher gives them a chance to ask them to silence and ask another friend. It is feared that students suffering from glossophobia do not develop optimally and continue into adulthood. The problem of this research is whether hypnotherapy regression therapy technique is effective to overcome glossophobia of grade VII students of SMP Negeri 3 Kediri ?. This research uses quantitative approach, design of SSD (Single Subject Design) with research subject 2 female students who identified glossophobic patients. The study was conducted in 7 meetings, 3 baseline phases and 4 intervention phases. Each meeting in the intervening phase applied regression therapy techniques. After this activity is completed, subjects are asked to fill out a glossophobia questionnaire in order to find out how effective the administration is in reducing glossophobia. This study concludes that hypnotherapy regression therapy techniques are effective for treating students with glossophobia. This is evidenced by the trend of the second graph of the subject declining and indicating which changes are positive. Based on these conclusions, it is suggested: (1) BK teachers can apply hypnotherapy regression therapy techniques to address student glossophobia, and (2) for advanced researchers it is advisable to examine this issue with a wider range of research areas.